Students' Science Process Skills and Understanding on Ohm's Law and Direct Current Circuit Through Virtual Laboratory Based Predict-Observe-Explain Model - Theo Jhoni Hartanto*; Pri Ariadi Cahya Dinata; Nadia Azizah; Annur Qadariah; Albi Pratama (Jurnal Pendidikan Sains Indonesia, 2023)
Many studies have found that good science process skills are correlated with understanding of concepts. Based on observations, many students have low understanding and processing skills, especially in physics subjects. This study aims to describe the impact of implementing the predict-observe-explain (POE) model assisted by virtual laboratory on the students’ science process skills and conceptual understanding of the topic of Ohm’s law and direct current (DC) electrical circuits. This study used a one-group pretest-posttest design involving 20 prospective teacher students in the Physics Education Program FKIP UPR. The sampling technique was saturated sampling. The instruments used were the conceptual understanding test and the performance test of science process skills. The conceptual understanding score was measured before and after the conducted learning and analyzed by N-Gain. While, data on students' science process skills were obtained from performance tests. The results showed an increase in the students’ conceptual understanding, which was indicated by an N-Gain score of 0.63 (moderate increase category). The aspects of the students’ science process skills observed in this study gained a good category. The results of the process skills test showed that 30% of students acquired science process skills with the category of “excellent”, 40% with the category of “good”, and 25% with the category of “adequate”. Based on results, it can be concluded that implementing a virtual laboratory-assisted POE can improve students’ conceptual understanding and science process skills, especially on the topic of Ohm’s law and dc electrical circuits